Heartbeat detector [videorecording (DVD)] = La question humaine - Klotz, Nicolas; Amalric, Mathieu, 1965-; Lonsdale, Michaël, 1931-2020-; Kalfon, Jean-Pierre, 1938-; Castel, Lou, 1943-; Spigarelli, Laetitia; Scob, Édith; Chuillot, Delphine; Emmanuel, François, 1952- (New Yorker Video, 2008)
A psychologist working for a large corporation discovers a startling link between big business and Nazism.